Engineering Design Methodology for Green-Field Supply Chain Architectures Taxonomic Scheme - Radanliev, Petar (2015)
Supply chain engineering requires a design that possesses the flexibility of a complex adaptive system, consisting of interlinking architecture, with external dimensions and system germane internal elements. The aim of this paper is to critically analyse the key supply chain concepts and approaches, to assess the fit between the research literature and the practical issues of supply chain architecture, design and engineering. The objective is to develop a methodology for strategy engineering, which could be used by practitioners when integrating supply chain architecture and design. Taxonomic scheme is applied to consider criteria for strategy architecture, hierarchical strategy integration design, strategy engineering, and integration of supply chain as a conceptual system. The results from this paper derived with the findings that the relationship between supply chain architecture, design and engineering is weak, and challenges remain in the process of adapting and aligning operations. This paper derived with a novel approach for addressing these obstacles, through a conceptual framework diagram and a new methodology, based on the taxonomic scheme. The novelty that derives from this paper is an engineering design methodology for integrating supply chain architecture and design, with criteria that enable decomposing and building a green-field (new and non-existent) supply chain as a system. The taxonomic scheme revealed a number of tools and mechanism, which enabled the development of a new methodology for engineering integrated architecture and design. The review derived with improvements to current and existing theories for analysing interdependencies within and between their individual contexts. This issue is addressed with a hierarchical method for network design, applied for building and combining the integration criteria. The resulting methodology is field tested through a case study with the slate mining industry in North Wales. DOI:10.12660/joscmv8n2p52-66URL: http://dx.doi.org/10.12660/joscmv8n2p52-66